ErratumAguilera, G., Mirande, J.M. & Azpelicueta, M.M. (2009) A new species of Cnesterodon (Cyprinodontiformes: Poeciliidae) from a small tributary of arroyo Cuñá-Pirú, río Paraná basin, Misiones, Argentina. Zootaxa, 2195, 3442. - Aguilera, G.; Mirande, J. M.; Azpelicueta, M. M. (Zootaxa, 2009)
(Erratum)